Quantitation of global histone post-translational modifications reveal anti-inflammatory epigenetic mechanisms of liquiritigenin based on the optimized super-SILAC strategy - Liu, Ping; Zhang, Jun; Zhang, Jingdan; Yuan, Yucheng; Liu, Zhiqing; Chen, Sixian; Chen, Kaifeng; Dong, Li; Cheng, Zhiyuan; Zhang, Yinan; Geng, Meiyu; Tan, Minjia; et al. (Frontiers in Cell and Developmental Biology, 2025)
Liquiritigenin (LIQ) is a dihydroflavonone monomer compound with a planar ring structure that exhibits potent anti-inflammatory activity. The post-translational modifications (PTMs) of histones are closely associated with inflammatory diseases. To explore the relationships between the anti-inflammatory effects and epigenetic regulatory mechanisms of LIQ, we optimized the super stable isotope labeling by amino acids in cell culture (super-SILAC) method combined with a compound stimulation strategy. Moreover, we evaluated the identification coverage and demonstrated high reliability as well as reproducibility of the optimized method at both the peptide and cellular lysate levels, which are promising for elucidating disease pathology and drug mechanisms. We further applied the method to a system-wide characterization of histone PTMs in M1 macrophages treated with LIQ. The quantitative results showed that H4K5ac, H4K16ac, H3K9ac, H3K27ac, and H2BK12ac are significantly upregulated. Transcriptome analysis revealed that LIQ could exert anti-inflammatory effects by modulating the histone PTMs and regulating gene expressions through the peroxisome proliferator-activated receptor (PPAR) signaling pathway. Collectively, we provide a sensitive and universal strategy for research on the epigenetic mechanisms of natural products as well as facilitate epigenetic understanding of LIQ in inflammatory therapies.